An appraisal of ginger (Zingiber officinale Rosc.) production in Sikkim, India - SINGH, PATIRAM PATIRAM, R C UPADHYAYA, L N (Journal of Spices and Aromatic Crops, 1995)
A general description of Sikkim and various aspects of cultivation and marketing of ginger (Zingiber officinale) in the state are discussed. The trend in production and major constraints in productivity are also dealt with.